In Asia, does higher social assistance spending mean better health?. - Handayani, Sri Wening (ADB Briefs., 2017)
For this study, the authors used three health outcomes which focus on indicators related to maternal and child health. It also used multiple linear regressions to test different models exploring the potential association of social protection spending of countries and health outcomes. In this paper, four models were used to examine the components of social protection spending that are mostly associated to better health outcomes.